Translators’ Work: A Combination of Linguistic, Communicative, and Mediation Activities - Abdulmajeed Al-Ogaili, Assist. Prof. Dr. Abdulsalam (Basra studies journal, 2026)
This study provides insights into linguistic, communicative and mediation activities in the translation process, illuminating the obstacles in the way of translators and providing avenues to overcome such factors. Translation is an intricate process that entails the negotiation of linguistic barriers (vocabulary differences, ambiguity, technical terminology), communicative barriers (cultural nuances, idiomatic expressions, tone and style), and mediation barriers (cultural mediation, contextual understanding, pragmatic mediation). This qualitative study analyzes translated terms and expressions (English-Arabic and Arabic-English). It is based on Wang's (2022) assumption that translation is a multifaceted activity that combines linguistic, communicative, and mediative elements to convey meaning accurately across languages and cultures. The findings of the study suggest that translators need to adopt a multilevel approach, incorporating different strategies like research, cultural adaptation, subject-matter expertise, in order to overcome these barriers and make translations that are accurate, culturally sensitive, and successfully convey the message.